Innovation in Judicial Police: New products for a new strategy - Zampronha, Luís Flávio (Advanced Notes in Information Science, 2023)
Recognizing innovation as a public authority tool of institutions, this article highlights the hindrances to innovation in the public security sector that will make it possible to use all operational capacity in organizations. Using the concepts and definitions established by the Oslo Handbook 2018, this article aims to analyze the problems related to innovation within the police sector and present guidelines for these innovations. The genuinely innovative field of judicial police is, therefore, related to the best possible use of the advantages promoted by new technologies and the growing flow of information inside law enforcement agencies, along with the production of new services and a reformulation of the judicial police’s business process.